CRC handbook of chemistry and physics - Lide, David R (CRC Press Taylor & Francis Group, 2008)
Presents major expansions and tables including properties of ionic liquids, solubilities of hydrocarbons in seawater, solubility of organic compounds in superheated water, nutritive value of foods and properties of organic semiconductors. This book features a foreword by 1996 Nobel Laureate in Chemistry.